Relationships between energy cost, swimming velocity and speed fluctuation in competitive swimming strokes - Barbosa, Tiago M. (2011)
The purpose of the study was to analyse relationships between total energy expenditure (Etot), energy cost (EC), intra-cycle variation of the horizontal velocity of displacement of centre of mass (dv) and mean swimming velocity (v). 17 Portuguese elite swimmers (4 at Freestyle, 5 at Backstroke, 4 at Breaststroke and 4 at Butterfly) were submitted to an incremental set of nx200-m swims. Bioenergetical and biomechanical parameters presented significant interrelationships. For pooled data, the relationship between Etot and v was r=0.59 (p<0.01), between EC and dv was r=0.38 (p<0.01) and the polynomial relationship, between dv and v was r=0.17 (p=0.28). Individual evaluation and identification of biomechanical critical points may help the swimmers to become more efficient at a certain swimming velocity.